A Novel Nonlinear Power Receiver Model for Resource Allocation in MIMO SWIPT Based on Input Power and Operating Frequency of Rectifier's Entropy - Shirichian, Mehdi; Moradi, Gholamreza; Shirazi, Reza Sarraf; Emadi, Mohammad Javad (IEEE transactions on vehicular technology, 2024)
One of the main challenges to develop the Internet of Things (IoT), mobile communication and unmanned aerial vehicle (UAV) devices is the limitation of the power supply. As a promising solution, simultaneous wireless information and power transfer (SWIPT) concept has been introduced while the performance highly depends on modeling the nonlinear characteristics of the receiver. In this article, a novel nonlinear model is presented for the DC output power of the rectifier as a function of the input power and the operating frequency. The proposed model is named Entropy model since the entropy of the input power and the operating frequency of the rectifier serve as indices of the rectifier's DC output power. Also, it can be used to compare the shape of various rectifiers' conversion efficiency. In addition, the proposed model is applicable to different operating frequency bands and works for a wide range of input power. The similarity of the proposed model with the measured data is more than 98%. To maximize the total received power over the frequency band by utilizing the proposed model, we solve a non-concave optimization problem subject to minimum required signal-to-interference-plus-noise ratios (SINRs) for three different receiver structures, i.e., power splitting, time switching and separated receivers. For all receivers, the non-concave optimization problem is transformed into a tractable form. Moreover, the ratio of the power splitter in the PS is optimized during solving resource allocation problems considering its effect on the total received power and SINR. The results demonstrate that resource allocation can significantly enhance the performance by use of the proposed nonlinear model rather than the conventional linear and nonlinear ones.